2022
DOI: 10.1088/1742-6596/2165/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of exposure to magnetic fields of extremely low frequency 300T and 500T in inhibiting the proliferation of pathogenic bacteria to increase physical resistance of vannamei shrimp

Abstract: Vannamei shrimp is a type of fish that rots easily, only able to survive about 6 hours at room temperature. This study aims to examine the effectiveness of exposure to an Extremely Low Frequency (ELF) magnetic field with an intensity of 300 T and 500 T in inhibiting the proliferation of pathogenic bacteria to increase the physical resistance of white vaname shrimp. The research design used a completely randomized design and was carried out at the Physics Laboratory of the Faculty of Teacher Training and Educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In general, Salmonella grows actively at a pH between 3.6-9.5 and is optimal at a pH close to normal [33]. It has been reported that exposure to the ELF magnetic field (500 µT, 50 Hz) for 120 minutes has been shown to suppress the proliferation of salmonella sp on vannamei shrimp [35].…”
Section: The Proliferation Of Salmonella Bacteriamentioning
confidence: 99%
“…In general, Salmonella grows actively at a pH between 3.6-9.5 and is optimal at a pH close to normal [33]. It has been reported that exposure to the ELF magnetic field (500 µT, 50 Hz) for 120 minutes has been shown to suppress the proliferation of salmonella sp on vannamei shrimp [35].…”
Section: The Proliferation Of Salmonella Bacteriamentioning
confidence: 99%
“…In fact, the exposition to the EMFs in the range of the interest don’t cause a negative effect on the patient and on the operator or other people according to the International Commission on Non-Ionizing Radiation Protection guidelines. The exposure to extremely low-frequency magnetic fields inhibits the proliferation of pathogenic microorganisms, such as Salmonella , E. coli or C. albicans 17 , 18 . The alternating magnetic field of 50 Hz affected the C. albicans viability, representing a new strategy for Candida infections 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, study findings indicate that the presence of extremely low-frequency (ELF) magnetic fields can impede the growth and reproduction of bacteria. For instance, research has demonstrated that being exposed to an extremely low frequency (ELF) magnetic field with a strength of 500 µT effectively hinders the growth of salmonella bacteria in Vanamae shrimp and cow's milk (Sudarti et al, 2022a;Sudarti et al, 2022b). A magnetic field strength of 900 µT can help preserve the vitamin C content in red wine by suppressing the growth of harmful bacteria (Sudarti et al, 2022c).…”
Section: Introductionmentioning
confidence: 99%